P51 Patient satisfaction during bronchoscopy: a quality improvement project. (12th November 2019) - Tonkin, J; Gannon, E; O'Connor, SJ
Abstract : We conducted a survey to learn about patients' experiences during bronchoscopy and to improve the patient experience. We surveyed patients, bronchoscopists and bronchoscopy nurses and repeated the assessment on patients 2 weeks later. Methods: We asked patients to rate using an analogue scale from 0–10 how well tolerated the bronchoscopy was (0 is well tolerated, 10 is poorly tolerated). Cough, breathlessness and overall satisfaction were assessed. We also asked for any comments about anything they wished they had known in advance. Results: 22 patients were surveyed at the time and 15 patients responded to the follow-up questionnaire. The mean satisfaction score at the time of bronchoscopy was 4.1 for cough, 4.2 for breathlessness and 4.0 overall. When repeated at 2 weeks the satisfaction scores were much improved at 1.9 for cough, 2.0 for breathlessness and 1.8 overall. The comments section provided interesting reading. Patients varied significantly in how prepared they felt they were for bronchoscopy. Some patients reported that the bronchoscopy leaflet 'gave [them] all the information [they] needed' while others claimed it was 'nothing like the procedure'. A common theme, however, when asked 2 weeks later that many patients did not recall being given their results. We noticed the sedation satisfaction scores between patients, bronchoscopy nurses and bronchoscopists varied significantly. There was no tendency for one group to report higher tolerability scores. Discussion and outcomes: Firstly, there is little correlation between patients, nurses and bronchoscopists reports of tolerability. A 'well-tolerated procedure' may have been satisfactory for sampling but not well tolerated by the patient. Secondly, satisfaction scores improved significantly on the second time of asking, we suggest this is due to the amnesic effect of benzodiazepines. Likely due to the effect of benzodiazepines, many patients did not recall having their results given to them after the procedure. We have created a 'normal letter' for patients with a normal examination to take home. In view of mixed opinions on pre-procedural preparation we developed a new patient information leaflet, focusing on areas the patients wished they had known beforehand. We continue to survey patients and staff for ongoing quality improvement.